Modernity, Reception, and Transformation in 19th-Century Ottoman Law: Transplantation of Concordat into Turkish Legal History - Ali Ekber Cinar (İstanbul Hukuk Mecmuası)
The 19th century was a watershed for the modernization of Ottoman law. The codifications and transplantations of the 19th century included Kânûnnâme-i Ticâret (1850), a commercial code transplanted from French law, more specifically Code de commerce (1807). The dominant view in the scholarly literature considers Kânûnnâme-i Ticâret to be a literal translation of France’s Code de commerce. In this paper, I revisit this view and examine (i) the relationship between Kânûnnâme-i Ticâret and Code de commerce and (ii) the modernization of Ottoman law in the 19th century, with a specific focus on the legal procedure known as concordat. I claim that Kânûnnâme-i Ticâret differed from Code de commerce in significant ways through the many additions, deletions, and modifications the Ottomans made, and my examination demonstrates that approximately a third of the articles present in Kânûnnâme-i Ticâret have no equivalent in Code de commerce. As a result, I argue that the Ottoman legislator did not hesitate to go beyond merely transplanting Europeanideas and ideals, taking the local context into consideration throughout the process of modernization and reception in the Ottoman Empire during the 19th century.